Desain Prototipe Automatic Trash Rake dengan Metode Gaussian Mixture Model - Erdani, Yuliadi; Candra, Wahyu Adhie; Aisyah, Aulia (Universitas Trunojoyo Madura, 2024)
Trash rake is a trash netting tool used to transport trash in rivers. In its application, the operation of trash rake is still mostly done manually by the operator. In this case, there is no effectiveness in terms of the use of human resources or the effectiveness of machines. Therefore, in this study, a development was made on an automatic trash rake machine that works automatically if the waste stuck on the trash rake machine has experienced density. The image processing method used is the Gaussian Mixture Model (GMM). Used camera to capture the image of the density of the trash. The captured image is processed by GMM method. Then the data is processed on a computer and the data is displayed on the web. Arduino will drive the motor on the trash rake machine automatically with the parameters of the waste density data. The results obtained, the system can detect the level of waste density with an accuracy of 67.5% in bright, dim and dark conditions with the camera position according to the object observation area. The trash rake machine can turn on and off automatically based on the detected waste density.